Optimalisasi Pemanfaatan Sekam Padi Menjadi Arang Sekam Untuk Mewujudkan Sinergi Pertanian Dan Lingkungan Di Desa Jayasampurna - Erlin Ayu Widiya; Mutia Hasti Hildani; Rafika Nurhaliza Fikriatul Faidah; Yeremia Prayogi; Hamdan Amaruddin (CV. ITTC INDONESIA, 2024)
This service activity focuses on optimizing the utilization of rice husks into husk charcoal in Jayasampurna Village as an effort to realize the synergy between the agricultural sector and environmental preservation. Rice husk, which is an abundant agricultural waste, often becomes an environmental problem due to improper handling. The main objective is to develop an effective method to convert rice husk into economically valuable and environmentally friendly husk charcoal. Utilization of rice husk into charcoal not only solves the waste problem, but also creates a closed nutrient cycle in the local agricultural system. Optimizing the utilization of rice husk into husk charcoal is a feasible and profitable strategy to be applied in other agricultural areas, with significant potential in improving economic and ecological sustainability. One form of good husk waste management is by making husk charcoal that has a selling and useful value. The need for activities focused on providing knowledge about the utilization of husk charcoal, how to convert rice husk waste into husk charcoal that has selling value and is expected to provide additional income for farmers in the Jayasampurna Village farmer group.